Prevalence of cestodes infection among school children of urban parts in Iraq - Sarah Basheer; Hadeel AlRubaye; Rusul Al-Juboori; Sarah khalaf (Microbes and Infectious Diseases, 2025)
Background: Tapeworms that are of zoonotic significance have been identified as a prominent issue in public health. Aim of study: the objective of the present study was to determine the occurrence rate of tapeworm infections among schoolchildren aged 5–12 living in metropolitan areas of Iraq over the period from September 2023 to December 2023. Methods: the stool examination utilized wet mount preparation in saline/iodine methods. The data was evaluated using suitable descriptive statistical methods. Results and conclusion: A total of 379 people were found to be infected with Helminthes, demonstrating a statistically significant difference among us (P≤0.01), as well as between males and females by using SAS.